Estudo de Marcas Expressivas da Voz em Três (3) Canções do Disco Clube da Esquina (1972): "Cais", "Pelo Amor de Deus" e "Os Povos" - Renato Frossard Cardoso (2021)
ABSTRACT This work aimed to study the expressive marks of Milton Nascimento's voice, in three (3) songs from the album Clube da Esquina (1972), by Milton and Márcio Borges. Our additional goal was to get acquainted and map the territory of Clube da Esquina and Milton Nascimento, researching their trajectory, from the beginning, until the accomplishment of the album. To accomplish that, first, listening of all tracks was achieved, in order to trace Clube da Esquina’s territory and identify distinctive traits of Milton Nascimento's voice. Then, the same was done with the selected songs, but in a more careful way. The choice of songs from this Clube da Esquina’s album, to study Bituca's voice, was motivated by the historical-cultural relevance and the prestige enjoyed by this music, in Brazil and abroad. It was also considered the fact that Milton Nascimento was the main responsible for the record. The concept of Expressive Marks was based on conjectures found in “Acerca do Ritornelo” (About the Ritornelo), by Deleuze and Guatarri (1997). In analogies, the authors refer to the characteristics and behavior of songbirds, comparing these traits to the expressive work of the artist. They relate the plumage, mating rites and the singing of certain birds, which distinguish them from others, with the expressive marks of the artist, that is, the voice of a singer, the brushstrokes of a painter, the steps of a dancer. According to this reasoning, the unique characteristics of each artist would correspond to their unique expressive marks, their digital impression. The theoretical framework used in this work had contributions from Tagg (2015), Ulhoa (1998), and others. Tagg's (2015) theoretical studies were used to identify and organize the elements that can highlight the presence of expressive marks. These are the parameters of musical expressiveness, classified into distinct groups that relate to different musical aspects: (1) time and speed and space; (2) timbre and intensity, (3) tone and tonality, and (4) wholeness. The conclusions indicate that, although the concept of expressive marks is related to the parameters of expressiveness, they do not exactly coincide with those patterns, but constitute distinctive marks of a certain singer, musician, or composer. In the case of Milton Nascimento, who is all three things at once, this became even more evident. Keywords: Expressive Marks, Voice, Clube da Esquina, Milton Nascimento.